RESULTS OF THE JOINT IAEA/ARPANSA INTERCOMPARISON EXERCISE ON WHOLE BODY DOSEMETERS FOR PHOTONS IN ASIA AND THE PACIFIC REGION. Issue 4 (12th October 2019) - Rizk, Chadia; Long, Stephen; Okyar, H Burçin; Baradaran, Samaneh; Al Fares, Elham; Sangau, John Konsoh; Shah, Buddha R
Abstract: An intercomparison exercise (IC) on whole body dosemeters to determine the quantity personal dose equivalent Hp (10) in photon radiation fields was jointly organised and conducted by the International Atomic Energy Agency (IAEA) and the Australian Radiation Protection and Nuclear Safety Agency (ARPANSA) for individual monitoring services (IMS) in Asia and the Pacific region. This was arranged to help the IMS in the region to achieve a more accurate dosimetry service and to improve their performance. Twenty-four IMS participated in this IC. Four sets of dosemeters were irradiated using X-ray and gamma radiation qualities at 0° and 20° angle of incidence, respectively. All the IMS provided results that were within the acceptable limits defined by the IAEA. However, only a minority of participants reported confidence intervals that included the reference dose, for each exposure scenario. For few systems, the overall performance could be significantly improved by reviewing calibration procedures.